(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2005)
The objective of the consultation was to provide advice to FAO and member governments on the impact of sanitary and phytosanitary standards on domestic livestock markets, and in particular to consider impacts on the poor who participate in livestock food chains, and the extent to which their concerns are being addressed. This publication describes the conclusions of the experts and observers of the consultation, and contributes to a global debate on the subject of livestock standards and market exclusion.
Keywords: Food industry and trade,Công nghiệp thực phẩm và thương mại; Sanitation,Vệ sinh môi trường